1989
DOI: 10.1055/s-2006-962081
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Liver Microsomal Membranes from Lipid Peroxidation by Garlic Extract

Abstract: Garlic extract, the ethanol-soluble fraction of garlic, prevented formation of thiobarbituric-acid-reactive substances and fluorescent substances during lipid peroxidation of rat liver microsomes. Lipid peroxidation increased the fluorescence anisotropy of 1,6-diphenyl-1,3,5-hexatriene labelled to the microsomes while this increase was prevented by the garlic extract. It thus seems probable that the garlic extract serves to maintain membrane fluidity. These effects were dependent on its concentration and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…A large number of pharmacological studies have shown that AGE exerts anti-fatigue, 11) anti-stress, 11) and anti-oxidation [8][9][10] effects. Ushijima et al have been reported that antifatigue effect of AGE is assessed by prolongation of running time under severe condition (30 m/min) using a treadmill in mice, suggesting that AGE prevents an acute physical fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of pharmacological studies have shown that AGE exerts anti-fatigue, 11) anti-stress, 11) and anti-oxidation [8][9][10] effects. Ushijima et al have been reported that antifatigue effect of AGE is assessed by prolongation of running time under severe condition (30 m/min) using a treadmill in mice, suggesting that AGE prevents an acute physical fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) Aged garlic extract (AGE), which is extracted for more than 10 months, is less irritating and toxic. 5,7) A large number of pharmacological studies have demonstrated that AGE possesses anti-oxidative, [8][9][10] anti-stress, 11) immunomodulating, 12) cardiovascular 13,14) and hepatoprotective 15,16) properties. Moreover, AGE has been shown to be superior to raw garlic in terms of its anti-oxidation properties, and amelioration of physiological and psychological stress.…”
mentioning
confidence: 99%
“…Garlic has been extensively studied and has been shown to have a number of medicinal properties, including immunomodulatory, hepatoprotective, antimutagenic, anticarcinogenic, and antioxidant effects. [3][4][5][6] Various garlic preparations and components have also been shown to have antioxidant activity, including the ability to lower reactive oxygen species in vivo. [7][8][9] We recently reported that using a model of DOX-induced heart damage in rats, pretreatment with aged garlic extract (AGE), a strong antioxidant, offered protection against DOXinduced myocardial cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction generates very reactive oxygen compounds, which in humans are responsible for causing or accelerating chronic disease states such as cardiovascular, neoplastic inflammatory and amyloidosis and aging. The antioxidant effects of garlic extracts and their components have been demonstrated and quantified by a variety of assays (Horie et al, 1989;Yamasaki et al, 1994). Ide et al (1996) reported that garlic and its major organosulphur constituents have a scavenging effect on hydrogen peroxide and inhibit the chain oxidation induced by a hydrophilic radical initiator.…”
Section: Introductionmentioning
confidence: 99%